2015
DOI: 10.1590/s1980-65742015000300012
|View full text |Cite
|
Sign up to set email alerts
|

Improving aerobic capacity through active videogames: A randomized controlled trial

Abstract: Abstract--The rate of peak workload improvement between different types of Active Video Games (AVG) in young sedentary adults was investigated. Aerobic capacity improvement after a 6-week intervention between AVG types was also compared. Twenty participants, after baseline assessments, were randomized into one of three parallel groups: structured AVG (n = 6), unstructured AVG (n = 7) and a control group (n = 7). Participants played their respective AVG 3 times a week for 6-weeks (30 minutes-session). The contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Previous studies have reported that a single AVG session induces a significant increase in HR, SBP, DBP, and hence in DP [1,2,4,5,23]. However, the PEH phenomenon in relation to AVG remains unclear.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous studies have reported that a single AVG session induces a significant increase in HR, SBP, DBP, and hence in DP [1,2,4,5,23]. However, the PEH phenomenon in relation to AVG remains unclear.…”
Section: Resultsmentioning
confidence: 96%
“…In order to get closer to the actual practice of physical exercises, the authors chose an AVG that had characteristics of functional training, as it is used in real life and has been applied in previous studies [2]. the structured Nike Kinect training ® game at the beginning and at the end of the session performs joint mobility to assist in the warm-up while providing functional movements such as squatting, pushing, jumping, forward, sideways, and backward, as presented in the literature [2]. the amount, duration, and speed of the exercises, as well as the interval were proposed by a 'functional physical evaluation' (ca.…”
Section: Rating Of Perceived Exertionmentioning
confidence: 99%
See 3 more Smart Citations